High Levels of Leucocyte and Thrombocyte Increasing COVID-19 Mortality Rate in RSUP Dr. M. Djamil Padang - Maulana Muharam; Sabrina Ermayanti; Afriani Afriani (Jurnal Respirologi Indonesia, 2023)
Background: Different leukocytosis, leucopenia, thrombocytosis, thrombocytopenia, and clinical severity appear in COVID-19's cases. This study is aimed to identify the association between leucocyte, thrombocyte, and clinical severity in COVID-19's outcome.Methods: A retrospective cohort study involving 121 patients with COVID-19 whom admitted from January to March 2021. Kruskal Wallis test was applied for analysis.Results: The majority of participants were female (55.4%), aged between 18-49 years old (42.1%), and had comorbidities (81.8%). Most participants had a normal range of leucocyte (57.9%), thrombocyte (62.8%), and moderate clinical severity (67.8%). Subjects with full recovery were 79.3%, with sequelae such as weakness, and/or shortness of breath 3.3%, and deceased 17.4%. Leucocyte and thrombocyte had an association with COVID-19 outcome (P=0.045 and P=0.030 respectively). Clinical severity had no association with COVID-19 outcome (P=0.304). Conclusion: Leucocyte and thrombocyte have an association with COVID-19 outcome. Clinical severity has no association with COVID-19 outcome.